La energía y su enseñanza - Espinel Rodríguez, Jhon David (Revista Científica, 2011)
It will present an approach to teaching about energy in the context of classical mechanics, led to dig with sixth graders from School San Bernardino. We developed an educational module designed from the conceptual reconstruction of the energy concept based on thework of Bernoulli, Leibniz and Joule. With the design and implementation of a teaching strategy are reflected classroom experiences such as statements issued by the students and drawings related to what they conceive of energy. These elements are useful for teachers since they are amenable to analysis and design tools identify the students have about energy. It enables teachers to generate pedagogical proposals based on previous ideas of students to bond with the concept of energy.